Social preferences under risk: The role of social distance - Natalia Montinari; Michaela Rancan (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2013)
In many different contexts individuals take decisions on the behalf of others. However, little is known about how this circumstance affects the decision making process and influences the ultimate individuals choices. In this paper, we focus on the context of investment decisions and study if (and how) lottery-type investment decisions made on behalf of another person differ i) compared to decisions which do not affect anyone else, and ii) depending on the social distance between who makes the decision and who is affected by it. Our results shows that social distance (i.e., whether the person affected by ones decision is an unknown stranger or a friend) is an important determinant when people decide on the behalf of others. Individuals are heterogeneous in their individual investment strategies but, on average, when deciding on behalf of a friend rather than only for themselves or a stranger, their behavior is closer to expected value maximization, exhibiting less risk taking. We interpret these findings as evidence of other regarding preferences affecting the decision making process in lottery-type decisions when the social distance is shortened.
Keywords: A13; C91; D64; D81; 330; friends; lottery-type investment; other regarding preferences; risk seeking; social distance